EVALUASI PELAKSANAAN PROGRAM TAHSIN METODE TILAWATI DENGAN MODEL CIPP DI SDIT AT-TAQWA SETU BEKASI - Zachroh, Siti Apipah; Haryono, Pauzan (LPPM Universitas Islam 45, 2025)
This study aims to evaluate the implementation of the Qur'anic recitation (tahsin) program using the Tilawati method at SDIT At-Taqwa Setu Bekasi through the CIPP evaluation model (Context, Input, Process, Product). The model is applied to comprehensively assess the success of the program from planning and implementation to its outcomes. This research adopts a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results indicate that, contextually, the program’s objectives align with the institution’s vision and are supported by adequate human resources, although some teachers have yet to obtain Tilawati certification. The learning process is designed to be engaging, systematic, and flexible, using melodic reading (nada) and small-group approaches. Evaluation of the product component reveals that more than 90% of students are able to read the Qur'an fluently and understand the basics of tajwid. While challenges were identified—such as time allocation issues, limited student textbooks, and difficulties in mastering melodic recitation—they did not significantly hinder the overall success of the program.